Fashioning Postfeminism : Spectacular Femininity and Transnational Culture - Dosekun, Simidele (Book collections on Project MUSE., 2020)
"Women in Lagos, Nigeria, practice a spectacularly feminine form of black beauty. From cascading hair extensions to immaculate makeup to high heels, their style permeates both day-to-day life and media representations of women not only in a swatch of Africa but across an increasingly globalized world. Simidele Dosekun's interviews and critical analysis consider the female subjectivities these women are performing and desiring. She finds that the women embody the postfeminist idea that their unapologetically immaculate beauty signals--but also constitutes--feminine power. As empowered global consumers and media citizens, the women deny any need to critique their culture or to take part in feminism's collective political struggle. Throughout, Dosekun unearths evocative details around the practical challenges to attaining their style, examines the gap between how others view these women and how they view themselves, and engages with ideas about postfeminist self-fashioning and subjectivity across cultures and class"--